Metabolic characterization of grapevine leaves: first clues towards biomarkers discovery - Maia, Marisa Raquel Gomes (2016)
Tese de mestrado, Bioquímica (Bioquímica), Universidade de Lisboa, Faculdade de Ciências, 2016